Meningkatkan Kemampuan Berbicara Siswa dalam Pelajaran Bahasa Inggris Menggunakan Aplikasi Robot Online - Nurhidayati Saleh (Indonesian Journal of Teacher Education, 2022)
This study aims to make students brave, confident in speaking English and able to express their sentences actively and creatively. The object of research is class X students of SMA Negeri 1 Cibinong, Bogor Regency. This research was made on the basis of the problems faced by the writer, namely when students were asked to speak in English or express learned expressions, most of them felt afraid, insecure, nervous and stuttered and there were even students who did not utter a single word. . This may be caused by internal and external factors from them. To overcome this problem the author tries to use the Android version of the online robot application (ESL ROBOT PRO) which is facilitated by the WWW.ESLFAST.COM website (an online robot used to learn English for students from countries where English is a second language or a foreign language). to practice communicating in English anytime and anywhere accessed via mobile phone (mobile phone). Even this application is very easy to download and there is no time limit for its users. The research method used is a qualitative descriptive method using an observation sheet containing a Speaking assessment rubric and an activity control observation sheet. Students are asked to send video recordings when they are talking to the robot and screenshots of the chat results. The observation results showed an increase in students' speaking skills and it was seen that most students were motivated, confident which made them creative, happy and able to apply what they had learned and even parents and other family members took advantage of this online robot application.